Talent management in the advertising industry - Tan, Wei Qi (2008)
This study focuses on gaining a better understanding of the management of creative talents within Singapore’s advertising industry. The main objective of this study is to propose a framework that links talent management to strategic management. The framework seeks to align the management of creative talents to the advertising agencies’ strategies and business outcomes. This study also identifies the fundamental characteristics and skills that practitioners regard as vital in achieving success on the job. It explores the factors that influence creative talents’ decision to stay with their current organisation. The findings are gathered through interviews conducted with six local advertising practitioners. The integration of these findings with the proposed framework will allow advertising agencies to maximise the returns on investment in talent management. This study discusses the implications of research in reducing the attraction-to-recruitment time of creative talents, designing curriculum to instill the fundamental characteristics and skills in future student population, and provision of incentives to retain creative talents in organisations. Potential avenues for future research were also proposed